Estimation of stress-sensitive reservoirs' initial parameters by automatic history matching - Elemo, Rufus; Knapp, Roy (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The rock and fluid properties of stress-sensitive reservoirs are dependent on the effective stress on the rock. Previous studies have shown that the currently available conventional well test methods are inadequate for Estimating the initial values of stress-sensitive reservoirs' parameter. This paper presents the results of a study maJe to estimate the initial values of some pertinent parameters for stress -sensitive reservoirs by using the technique of history matching. In automatic history matching, mathematical programming methods are used to optimize a criterion function which is a mathematical formula that characterizes the difference between the calculated model behavior and the observed behavior of the real physical system. The history